(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Shakespeare’s dramas are among the most studied and performed literary works globally, characterized by their rich linguistic and stylistic intricacy. This article explores the defining linguistic features of Shakespeare’s texts, including Early Modern English grammar and syntax, wordplay, metaphor, and rhetorical techniques. It also examines how these elements influence meaning, character development, and audience reception. Furthermore, it discusses the challenges translators face when rendering Shakespeare’s texts into Uzbek, particularly in maintaining their poetic rhythm, cultural references, and dramatic intensity. The study highlights the importance of balancing literal accuracy and creative adaptation to ensure that Shakespeare’s linguistic artistry is effectively conveyed in Uzbek translations.